The Influence of Corporate Governance in Chinese Companies on Discretionary Accruals and Real Earnings Management - Hsu, Ming-Feng; Wen, Shiow-Ying (Asian Economic and Financial Review, 2015)
This study investigates the influence of ownership structure and board characteristics on discretionary accruals and real earnings management using the data of A-shares in Chinese Shanghai and Shenzhen Stock Exchange Securities Market from 2002 to 2012. The empirical results show that institutions with high shareholding proportion or great shareholding concentration give managers incentives to manipulate discretionary accruals for short-term profitability. The more substantial insider holdings can effectively regulate managers and forbid them to manipulate real earnings and to cause the detriment of firm value. Regarding the board structure, establishing independent directors is ineffective in monitoring the earnings management behavior of the managers. With the duality of the board chairman and CEO, the company would manipulate discretionary accruals to meet its goal because of entrenchment effect. The larger the board size, the more ability for the board to monitor whether the managers conduct earnings management behavior or not.